Reduction in the desaturation capacity of the liver in mice subjected to high fat diet: Relation to LCPUFA depletion in liver and extrahepatic tissues. (July 2015) - Valenzuela, Rodrigo; Barrera, Cynthia; Espinosa, Alejandra; Llanos, Paola; Orellana, Paula; Videla, Luis A.
Abstract: α-Linolenic (ALA) and linoleic (LA) acids are precursors of long chain polyunsaturated fatty acids (LCPUFAs), FAs with important biochemical and physiological functions. In this process, desaturation reactions catalyzed by Δ5- and Δ6-desaturase play a major role, enzymes that are subjected to hormonal and dietary regulation. The aim of this study was to assess the influence of a high fat diet (HFD) on activity of liver Δ5 and Δ6 desaturases, in relation to LCPUFA composition in liver and extrahepatic tissues. Male C57BL/6J mice received control diet (CD) (10% fat, 20% protein and 70% carbohydrate) or high fat diet (HFD) (60% fat, 20% protein, and 20% carbohydrate) for 12 weeks. After this time, blood and liver samples were taken for metabolic, morphologic, inflammatory, oxidative stress and desaturase activity assessment, besides FA phospholipid analysis in erythrocytes, heart, adipose tissue and brain. HFD significantly increased hepatic total fat, triacylglycerides and free FA content with macrovesicular steatosis and oxidative stress enhancement, concomitantly with higher fasting serum glucose and insulin levels, HOMA, and serum cholesterol, triacylglycerols, TNF-α, and IL-6. Diminution in liver Δ5- and Δ6-desaturase activities and LCPUFA depletion were induced by HFD, the later finding being also observed in extrahepatic tissues. In conclusion, HFD-induced reduction in the bioavailability of liver LCPUFA is associated with defective desaturation of ALA and LA, with Δ5- and Δ6-desaturase activities being correlated with insulin resistance development. Data analyzed point to the liver as a major organ responsible for extrahepatic LCPUFA homeostasis, which is markedly deranged by HFD.